Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2478/10004-1254-63-2012-2190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Myosmine on Antioxidative Defence in Rat Liver

Abstract: Myosmine [3-(1-pyrrolin-2-yl) pyridine] is an alkaloid structurally similar to nicotine, which is known to induce oxidative stress. In this study we investigated the effects of myosmine on enzymatic and nonenzymatic antioxidative defence in rat liver. Wistar rats received a single i.p. injection of 19 mg kg -1 of myosmine and an oral dose of 190 mg kg -1 by gavage. Nicotine was used as a positive control. Through either route of administration, myosmine altered the hepatic function by decreasing the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…The decreased levels of GSH in nicotine-treated rats indicate that GSH protects membrane lipids from oxidation by scavenging free radicals, passing from reduced to oxidized form (GSSG) (14,31,35 (8), thereby decreasing its activity as we observed in our study. Other studies (31,35) have also demonstrated the depletion of SOD and CAT in some organs of nicotine-treated rats.…”
Section: Gsh and Antioxidant Enzymessupporting
confidence: 56%
“…The decreased levels of GSH in nicotine-treated rats indicate that GSH protects membrane lipids from oxidation by scavenging free radicals, passing from reduced to oxidized form (GSSG) (14,31,35 (8), thereby decreasing its activity as we observed in our study. Other studies (31,35) have also demonstrated the depletion of SOD and CAT in some organs of nicotine-treated rats.…”
Section: Gsh and Antioxidant Enzymessupporting
confidence: 56%
“…The regulation of NF-κB signaling directly affects expression of pro-inflammatory cytokines and inflammatory mediators involved in immune response. 33,34 Our findings showed that the SA concentration dependently suppressed LPS-induced IL-6 transcription (Fig. 2) on NF-κB activation, as evidenced by the decrease in NF-κB DNA-binding ability and reporter gene activity (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have documented the antioxidant. 33 and hepatoprotective 7,10 activities of SA, but its immuno-modulatory effects have not been investigated. This study elucidated SA anti-inflammatory activity using LPSstimulated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous experiments [57, 58] enhanced level of tissue lipid peroxides in nicotine treated rats (1 mg/kg i.p; 6,5 mg/kg p.o.) has been shown to be accompanied by a significant decrease in the levels of GSH, glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) and increased glutathione reductase (GR) activity in Wistar rat liver.…”
Section: Nicotinementioning
confidence: 99%